Characterizing differences in Shiga toxin-producing Escherichia coli (stec) attachment to pre-rigor and chilled beef carcass surfaces - Schwan, Carla Luísa (Kansas State University, 2015)
The USDA declared seven STEC serotypes to be adulterants in raw, non-intact beef products due to their severe health implications. STEC contamination of carcasses is most likely to occur during hide removal. This study evaluated the efficiency of a mixed STEC-7 inoculum to attach to raw beef carcasses (predominantly lean muscle and adipose tissue), and compared the efficacy of 4.5% lactic acid (LA) to a water (W) spray to reduce STEC populations. Four carcass contamination scenarios, representing potential points whereby STEC could come into contact with raw beef surfaces during slaughter operations, were evaluated: (A) pre-rigor surface STEC inoculated (ca. 7 log cfu/cm[superscript]2), 30-min ambient temperature attachment, spray with LA or W; (B) pre-rigor inoculated, 24-h chilled attachment, spray; (C) tissue chilled 24 h, inoculated, 30-min attachment, spray; and (D) tissue chilled 24 h, rewarmed to 30°C, inoculated, 30-min attachment, spray. Predominantly lean muscle and adipose tissue were collected from four fed cattle immediately after harvest and assigned to the four scenarios for STEC inoculation, followed by a post-inoculation water (control) or LA spray. Tissue excision samples were collected pre- and post-treatment and analyzed to enumerate STEC-7 populations. Data were collected in a completely randomized design and analyzed using a mixed-model ANOVA. Pairwise comparisons of treatment means were made at α = 0.05 with p-values adjusted using Tukey-Kramer. Initial STEC attachment levels to predominantly lean muscle and adipose tissues were not significantly different across all scenarios. Scenarios C and D showed greater STEC attachment compared to scenarios B and A. The LA spray reduced STEC levels more effectively than water across all scenarios. A significant treatment by tissue type interaction was observed for STEC reductions. A greater STEC reduction was observed for adipose tissue than for predominantly lean muscle when lactic acid spray was applied. A significant treatment by scenario interaction was observed for STEC reductions. Scenarios A and B presented greater log reductions (1.77 ± 0.27 and 1.85 ± 0.25 log CFU/cm[superscript]2, respectively) than scenario C (1.04 ± 0.10 Log CFU/cm[superscript]2). LA spray presented the same level of effectiveness when applied to pre-rigor warm tissues and chilled tissues for reducing STEC. Greater post-LA spray reductions were observed when STECs were inoculated onto pre-rigor meat surfaces and submitted to a 24 h chill cycle, suggesting that cold storage temperatures (~2 °C) may stress or injure the STEC cells prior to subsequent antimicrobial spray applications to chilled surfaces. For laboratory studies, consideration must be given to when inocula are applied to tissue surfaces to accurately determine and/or compare the effectiveness of antimicrobial treatments. These findings provide insight to beef processors and researchers regarding inoculation protocols for comparative validation studies, and potential impacts on microbiological results from application of antimicrobial interventions at different points during raw beef processing.
Keywords: Attachment; Lactic acid; Beef surfaces; Shiga toxin-producing Escherichia coli; E. coli; Pre-rigor meat; Animal Sciences (0475); Food Science (0359)